Intracranial Hemorrhage in Systemic Lupus Erythematosus Associated with an Autoantibody against Factor XIII - Lorand, Laszlo; Velasco, Pauline T.; Hill, John M.; Hoffmeister, Karen J.; Kaye, Fredric J. (Thrombosis and Haemostasis, 2002)
Intracranial hemorrhage in a young woman with systemic lupus erythematosus necessitated two surgical evacuations. In the absence of a family history of bleeding, clot solubility in urea suggested a factor XIII (FXIII) inhibitor. The patient’s IgG bound well to the virgin and the thrombin-modified zymogen ensemble (A2B2 and A2’B2) and to the free rA2 but reacted poorly with the thrombin-modified rA2’. Since the IgG did not block the thrombin-catalyzed proteolysis of A subunits nor the dissociation of the A2’B2, its action might be to interfere with the release of activation peptides from the thrombincleaved zymogen, hindering the conformational change necessary for generating FXIIIa.Treatment with cryoprecipitate and cyclophosphamide arrested the hemorrhage and almost neutralized the antibody so that the patient’s clot became insoluble in urea and showed a close to normally cross-linked γ-γ and αn fibrin chain profile. Nevertheless, she still has detectable anti-FXIII antibody and may be at risk for hemorrhage.
Keywords: Lupus; factor XIII autoantibody